1997
DOI: 10.1021/bi970014q
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Localization, Topology, and Mutual Stabilization of thernfABCGene Products inRhodobacter capsulatusand Implications for a New Family of Energy-Coupling NADH Oxidoreductases

Abstract: The rnf genes in Rhodobacter capsulatus are unique nitrogen fixation genes that encode potential membrane proteins (RnfA, RnfD, and RnfE) and potential iron-sulfur proteins (RnfB and RnfC). In this study, we first analyzed the localization and topology of the RnfA, RnfB, and RnfC proteins. By activity and immunoblot analysis of expression of translational fusions to Escherichia coli alkaline phosphatase, RnfA protein was shown to span the chromatophore membrane with its odd-numbered hydrophilic regions exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 65 publications
6
103
0
Order By: Relevance
“…3A). The Rnf complex was first described in Rhodobacter capsulatus (34), where it is proposed to encode a six-subunit (20) membrane-bound complex (RnfABCDGE) oxidizing NADH and reducing a ferredoxin which then donates electrons to nitrogenase (23,34). It is further proposed that the thermodynamically unfavorable reverse electron transport is driven by an electrochemical gradient (27,33).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). The Rnf complex was first described in Rhodobacter capsulatus (34), where it is proposed to encode a six-subunit (20) membrane-bound complex (RnfABCDGE) oxidizing NADH and reducing a ferredoxin which then donates electrons to nitrogenase (23,34). It is further proposed that the thermodynamically unfavorable reverse electron transport is driven by an electrochemical gradient (27,33).…”
Section: Resultsmentioning
confidence: 99%
“…The subunits of the Rnf complex from R. capsulatus (Rc-Rnf) have been previously characterized (20,23), predicting functions for subunits of the M. acetivorans Rnf complex (Ma-Rnf) encoded by MA0658-0665 (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RnfA, RnfD, and RnfE are predicted to be transmembrane proteins, whereas RnfC is a soluble protein and RnfB and RnfG are predicted to be associated with the membrane (25). In Rnf complexes indications of flavin mononucleotide and NADH binding sites were found, as were motifs typical of [4Fe-4S]-type ferredoxin-like domains (30). Bioinformatic analyses revealed that Rnf and Na ϩ -pumping NADH:quinone oxidoreductase (Nqr) complexes are similar (25), which leads to the idea that Rnf complexes could function as Na ϩ pumps as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the phototrophic nonsulfur bacterium Rhodobacter capsulatus a set of nitrogen-regulated genes, the rnf genes, as shown by mutational studies, encode proteins involved in electron transfer to nitrogenase (25,30,42,45). The membrane protein complex encoded by the rnf genes shows similarity to sodium-dependent NADH oxidoreductases and is thought to drive the NADH-dependent reduction of ferredoxin I (the fdxN gene product) by utilizing the PMF derived from the photosynthetic activities of the cell.…”
mentioning
confidence: 99%